A discourse and content analysis of how nursing is framed in the mainstream press in South Africa: January-June, 2010 - Van Zyl, Greer (My University, 2012)
Introduction: Globally and locally, the status of nurses and their profession is diminishing, ascribed partly due to the image of nursing portrayed in the media of a profession with heavy workloads, poor pay and no longer considered a career of choice. In South Africa, the increased disease burden due to HIV/AIDS and tuberculosis, together with a deteriorating health system and significant inequities in terms of nurse distribution, has led to grave public concerns about the profession. The media play a key role in national development, helping to shape public perceptions by influencing how society understands events. This cross-sectional study aimed to explore how nursing is framed in the mainstream press over a six-month period in 2010 using mixed methods of a quantitative content analysis and a qualitative discourse analysis. Methodology This cross-sectional study used a mixed method approach of both quantitative and qualitative methodologies. The content of all articles mentioning „nurse‟ or „nursing‟ from the press cutting agency Monitoring South Africa (1 January – 30 June 2010) was analysed, yielding a total of 242 articles. From these, 91 articles were purposively selected for the qualitative discourse analysis. A data coding sheet was developed to capture key dimensions from each article for the quantitative content analysis. Both descriptive and inferential analysis was carried out. For the qualitative discourse analysis press cuttings were converted and coded, and then thematic analysis was carried out Results The results of the quantitative analysis found that nursing is not well covered in the South African lay press, and when it is featured, articles appear in community publications with small circulations. Most articles on nursing were prominent (ie. full-length) and positive. International Nurses‟ Day (IND) was seen to influence the proportion of nursing articles with more than double the number of articles appearing in May compared to the total average of other months, and all coded „positive‟. However, when IND was excluded from analysis, negative articles were dominant, mainly around strikes and unprofessional behavior which featured in daily and larger circulation newspapers. In keeping with international literature, strikes as a theme received the most coverage, but unique to this study was the finding that nursing neglect or unprofessionalism received almost as much coverage as strikes, featuring in the majority of page 1 articles and in publications with large circulations. 5 Regarding voice, this study found that nurses were quoted in just over a quarter of articles which featured quotes, but that spokespeople were quoted twice as often, remarkably so even for IND. Most nurse quotes were around strikes and poor working conditions. Nurses were quoted more frequently in community newspapers and in Western Cape newspapers. Doctors were seldom quoted, and 90% of patient quotes were negative. While females were quoted first in the majority of articles, a third of their quotes were anonymous, mainly around negative topics such as labour, protest action and service delivery, indicating their fear of reprisal from their institutions. Males were quoted more often in second and third quotes of articles, with the extent of quotes approximately in proportion to their numbers in the profession. The results of the qualitative discourse analysis revealed a profession groaning under the weight of a crumbling health system. Articles on the working conditions, salaries and shortages of nurses were mostly sympathetic, but when nurses „went too far‟, they were portrayed as unprofessional, negligent and abusive. Nurses were also not taken seriously when they raised the alarm about deteriorating health systems, which is disturbing when they are at the forefront of healthcare delivery. Very few articles dealt with nursing as a profession or academic nursing in any detail. Although there were more positive than negative articles, and IND garnered significant positive coverage for the profession with nearly a third of all articles appearing in May when IND is celebrated, the lasting impression is that of negative coverage, particularly from the discourse on patient abuse, neglect or abandonment during strikes. Nurse voices are notably absent from these articles. Conclusion South African nursing would benefit from media advocacy and partnerships to promote the profession. As the majority workforce which undertakes essential, life-giving tasks, nurses are the backbone of the healthcare system and critical contributors to quality health care. Their place at the policy table and space in the press is well overdue.
M.P.H., Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: Nursing Care; Public Opinion--South Africa